Evaluation of 19 years of international external proficiency testing for high-resolution HLA typing - Voorter, C. E. M.; Groeneveld, L.; Heidt, S.; Wieten, L. (Frontiers in Genetics, 2024)
The international High Resolution external proficiency testing (EPT) started in 2004 with high resolution typing of HLA class I (HLA-A,B,C) and HLA class II (HLA-DRB1, DRB345, DQB1 and DPB1) alleles, since possibilities for such an EPT within Europe were limited and all existing EPTs at that time made use of comparison of HLA typing results without a reference. This EPT was set up as a collaboration between the HLA laboratory of Leiden, providing DNA samples to the participants, and the laboratory of Maastricht, performing the high resolution typing as reference result and evaluating the results of all participants according to the prevailing EFI standards. Once a year 12 samples were sent to the participating laboratories, and evaluation and certificates were provided at the end of that same year. During the years, the EPT was extended to low resolution HLA class I and II typing, high resolution typing including DQA1 and DPA1 and allelic resolution typing for HLA class I, the latter one being unique in this field. Evaluation of the high resolution typing results of the last 19 years showed a clear increase in the number of loci tested by the participating laboratories, as well as a clear change of method from Sanger sequencing with additional other techniques (SSO/SSP) to the nowadays widely used next generation sequencing method. By strictly using the EFI rules for high resolution HLA typing, the participants were made aware of the ambiguities within exons 2 and 3 for class I and exon 2 for class II as well as the presence of null alleles even in a two field HLA typing. There was an impressive learning curve, resulting in >98% correctly typed samples since 2017 and a 100% fulfillment of EFI rules for all laboratories for all loci submitted in the last two years. Overall this EPT meets the need of an EPT for high resolution typing for EFI accreditation.